Lithium tantalate wafer and preparation method of lithium tantalate wafer
By adjusting the lithium ion concentration in the lithium tantalate polycrystalline material and using platinum wire isolation layer and heat treatment technology, lithium tantalate wafers with lithium ion concentration of 49.6% to 49.75% were prepared, and the acoustic performance of lithium tantalate crystals was solved. The problem is that high electromechanical coupling coefficient and low temperature drift coefficient are achieved to meet the performance needs of the 5G era.
Patent Information
- Application Number
- CN202411177790.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-27
AI Technical Summary
The acoustic performance of existing lithium tantalate crystals is insufficient, especially the high temperature drift coefficient and low electromechanical coupling coefficient, which is difficult to meet the performance requirements of surface acoustic wave filters in the 5G era.
By adjusting the lithium ion concentration in the lithium tantalate polycrystalline material, lithium tantalate wafers with lithium ion concentrations of 49.6% to 49.75%, platinum wire isolation layer and heat treatment technology are used to control the lithium content and diffusion conditions, and high electromechanical coupling is prepared. Lithium tantalate chip with coefficient and low temperature drift coefficient.
It has achieved the improvement of the acoustic performance of lithium tantalate wafers, with low cost and high yield, which can better adapt to the performance requirements of surface acoustic wave filters in the 5G era.
Smart Images

Figure CN119194614A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of crystal materials, and specifically relates to a lithium tantalate wafer and a method for preparing the lithium tantalate wafer. Background Art
[0002] Lithium tantalate crystal is an important inorganic nonlinear optical crystal with excellent acoustic properties such as low acoustic loss and high-voltage electrical coupling coefficient. It is widely used in the production of surface acoustic wave filters. With the development of 5G, surface acoustic wave filters face higher performance requirements. Therefore, improving the acoustic performance of lithium tantalate crystals is an urgent problem to be solved in the 5G era.
[0003] The ratio of lithium to tantalum in the currently widely used isocratic lithium tantalate crystals is 48.75:51.25. Due to the low lithium content, the temperature drift coefficient of isocratic lithium tantalate crystals is relatively high and the electromechanical coupling coefficient is relatively low. The existing technology for improving the acoustic performance of isocratic lithium tantalate crystals includes bonding isocratic lithium tantalate wafers to silicon wafers, and using silicon wafers to limit the thermal expansion of isocratic lithium tantalate wafers, thereby reducing the temperature drift coefficient of the bonded wafers. This method has the disadvantages of high cost and low yield. Another method is to make stoichiometric lithium tantalate wafers, fill the lithium vacancies in the lithium tantalate crystals with lithium ions, and prepare near-stoichiometric lithium tantalate wafers with a lithium and tantalum ratio close to 1:1. The acoustic performance of the lithium tantalate wafers obtained in this way still needs to be improved. Summary of the invention
[0004] The technical problem to be solved by the present application is to provide a lithium tantalate wafer and a method for preparing the lithium tantalate wafer, so as to prepare a lithium tantalate wafer with a high electromechanical coupling coefficient and a low temperature drift coefficient, and improve the acoustic performance of the lithium tantalate wafer.
[0005] In order to solve the above-mentioned problem of the present application, the present application provides a lithium tantalate wafer, characterized in that the lithium ion concentration inside the lithium tantalate wafer is 49.6% to 49.75%.
[0006] The lithium tantalate wafer provided in the present application has a lower production cost and a higher yield rate than a bonded wafer, and has a higher electromechanical coupling coefficient and a lower temperature drift coefficient and better acoustic performance than a near-stoichiometric lithium tantalate wafer.
[0007] In order to solve the above-mentioned problems of the present application, the present application also provides a method for preparing a lithium tantalate wafer, which is characterized by comprising: evenly placing 50g to 200g of lithium tantalate polycrystalline material into the bottom of a first crucible; placing two platinum wires above the lithium tantalate polycrystalline material, and placing a lithium tantalate wafer with the same composition on the platinum wires; placing the sealed first crucible in a second crucible whose bottom is covered with lithium tantalate polycrystalline material; placing the second crucible in a heat treatment furnace, and heat treating it at a temperature of 1190°C to 1320°C for 10 to 150 hours for diffusion to obtain a finished lithium tantalate wafer.
[0008] The solution provided in the present application adjusts the lithium ion concentration and mass in the lithium tantalate polycrystalline material, and then adjusts the lithium content in the lithium tantalate wafer with the same composition, so as to prepare lithium tantalate wafers with a lithium ion concentration of 49.6% to 49.75%, thereby improving the acoustic performance of the lithium tantalate wafers.
[0009] As an improvement of the preparation method of the lithium tantalate wafer mentioned above, the present application further includes: annealing the lithium tantalate wafer with the same composition at a temperature of 500°C to 800°C before placing the lithium tantalate wafer with the same composition on the platinum wire.
[0010] As an improvement of the preparation method of the above-mentioned lithium tantalate wafer in the present application, before placing the lithium tantalate wafer with the same composition on the platinum wire, it also includes: growing a lithium tantalate single crystal with the same composition by using a pulling method; and pre-treating the lithium tantalate single crystal with the same composition to obtain the lithium tantalate wafer with the same composition.
[0011] As an improvement of the above-mentioned method for preparing lithium tantalate wafers in the present application, before placing the sealed first crucible in the second crucible whose bottom is covered with lithium tantalate polycrystalline material, it also includes: placing a crucible cover above the first crucible for sealing; after placing the sealed first crucible in the second crucible whose bottom is covered with lithium tantalate polycrystalline material, it also includes: placing a third crucible upside down on the sealed first crucible to isolate the first crucible from the lithium tantalate polycrystalline material.
[0012] As a preferred choice of the lithium tantalate polycrystalline material of the present application, the molar ratio of lithium to tantalum in the lithium tantalate polycrystalline material is (50-70):(50-30).
[0013] As a preferred choice of the lithium tantalate wafer with the same composition in the present application, the thickness of the lithium tantalate wafer with the same composition is 0.2 mm to 1.2 mm.
[0014] The beneficial effects of this application are:
[0015] The solution provided in the present application adjusts the lithium ion concentration and mass in the lithium tantalate polycrystalline material, and then adjusts the lithium content in the lithium tantalate wafer with the same composition, so as to prepare lithium tantalate wafers with a lithium ion concentration of 49.6% to 49.75%, thereby improving the acoustic performance of the lithium tantalate wafers.
[0016] The lithium tantalate wafer disclosed in the present application successfully prepares a lithium tantalate wafer with a high electromechanical coupling coefficient and a low temperature drift coefficient by controlling the internal lithium ion concentration to 49.6% to 49.75%. The lithium tantalate wafer has better acoustic performance than the existing lithium tantalate wafer and can better meet the higher performance requirements of surface acoustic wave filters in the 5G era. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of a method for preparing a lithium tantalate wafer in an embodiment of the present application;
[0018] Figure 2 It is a connection schematic diagram of an experimental device used in a method for preparing a lithium tantalate wafer in an embodiment of the present application;
[0019] Description of reference numerals:
[0020] 1. First crucible; 2. Crucible cover; 3. Second crucible; 4. Third crucible; 5. Platinum wire; 6. Lithium tantalate wafer. DETAILED DESCRIPTION
[0021] The embodiments of the technical solution of the present application will be described in detail below. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0022] The present application provides a method for preparing a lithium tantalate wafer, comprising uniformly placing 50 g to 200 g of lithium tantalate polycrystalline material at the bottom of a first crucible; placing two platinum wires above the lithium tantalate polycrystalline material, and placing a lithium tantalate wafer with the same composition on the platinum wires; placing the sealed first crucible in a second crucible whose bottom is covered with lithium tantalate polycrystalline material; placing the second crucible in a heat treatment furnace, heat treating at a temperature of 1190° C. to 1320° C. for 10 to 150 hours for diffusion, to obtain a finished lithium tantalate wafer.
[0023] Specifically, the role of platinum wire is to prevent direct contact between lithium tantalate wafers and lithium tantalate polycrystalline materials of the same composition. As a physical isolation layer, platinum wire can prevent excessive reaction between lithium tantalate wafers and lithium tantalate polycrystalline materials of the same composition, and avoid excessive doping of lithium tantalate wafers of the same composition. In addition, platinum wire can help evenly distribute lithium tantalate polycrystalline materials, ensuring uniform thickness and composition of the diffusion layer at various locations on the surface of lithium tantalate wafers of the same composition.
[0024] The first crucible and the second crucible are ceramic crucibles, and the diameter of the second crucible is larger than that of the first crucible. During the high-temperature diffusion process in the heat treatment furnace, lithium may volatilize in the form of vapor. Sealing the first crucible can reduce the escape of lithium to the outside during the reaction process and ensure the concentration of lithium in the reaction atmosphere.
[0025] In some embodiments, before placing the sealed first crucible in the second crucible whose bottom is covered with lithium tantalate polycrystalline material, it also includes: placing a crucible cover on the first crucible for sealing; after placing the sealed first crucible in the second crucible whose bottom is covered with lithium tantalate polycrystalline material, it also includes: placing a third crucible upside down on the sealed first crucible to isolate the first crucible from the lithium tantalate polycrystalline material.
[0026] Specifically, see Figure 2 As shown in the connection schematic diagram, this embodiment uses a crucible cover that matches the shape of the above-mentioned first crucible to seal the opening of the first crucible to reduce the escape of lithium to the outside. In order to prevent external impurities from entering the first crucible during the diffusion process and affecting the purity and quality of the lithium tantalate crystals, this embodiment also provides a third crucible that is inverted on the sealed first crucible to further isolate the first crucible. Optionally, in order to ensure sealing, the gap between the above first crucible and the third crucible can be filled with lithium tantalate polycrystalline material to achieve a sealing effect.
[0027] In some embodiments, before placing the lithium tantalate wafer with the same composition on the platinum wire, it also includes: annealing the lithium tantalate wafer with the same composition at a temperature of 500° C. to 800° C.
[0028] Specifically, annealing the isocratic lithium tantalate wafer before the diffusion process can reduce the stress inside the isocratic lithium tantalate wafer caused by pretreatment, thereby improving the quality of the isocratic lithium tantalate wafer.
[0029] In some embodiments, before placing the lithium tantalate wafer with the same composition on the platinum wire, the method further includes:
[0030] Growing lithium tantalate single crystals with the same composition by Czochralski method;
[0031] The lithium tantalate single crystal with the same composition is pretreated to obtain the lithium tantalate wafer with the same composition.
[0032] Specifically, growing isomeric lithium tantalate single crystals by the Czochralski method is a conventional method for preparing isomeric lithium tantalate crystals in the art. In this embodiment, isomeric lithium tantalate wafers are prepared by pretreating isomeric lithium tantalate single crystals, wherein the pretreatment method includes cutting, rounding, slicing and chamfering the isomeric lithium tantalate single crystals to make them into circular isomeric lithium tantalate wafers with a thickness of 0.2 mm to 1.2 mm, and further wiping dust on the surface of the isomeric lithium tantalate wafers with alcohol to ensure the cleanliness of the surface and avoid introducing impurities that affect subsequent reaction processes.
[0033] According to the implementation method provided by the present application, some specific experiments have been conducted on the present application, that is, by adjusting the lithium ion concentration and quality in the lithium tantalate polycrystalline material, and then adjusting the lithium content in the lithium tantalate wafer with the same composition, an embodiment of preparing lithium tantalate wafers with different lithium ion concentrations. It can be seen from these embodiments that the scheme provided by the present application has achieved good results. It should be noted that the following embodiments are only used to illustrate the present invention in detail and do not limit the scope of protection of the invention in any way.
[0034] Example 1
[0035] S1. Evenly place 120 g of lithium tantalate polycrystalline material having a molar ratio of lithium to tantalum of 55:45 into the bottom of the first crucible;
[0036] S2, placing two platinum wires on the lithium tantalate polycrystalline material, and placing a Y42° lithium tantalate wafer with a thickness of 0.5 mm obtained by annealing at 500° C. for 20 hours on the platinum wires;
[0037] S3, placing the sealed first crucible in a second crucible with the bottom covered with lithium tantalate polycrystalline material;
[0038] S4. Placing the second crucible in a heat treatment furnace, heat treating at 1250° C. for 60 hours for diffusion, and obtaining a finished lithium tantalate wafer with a Li ion concentration of 49.75% inside the wafer.
[0039] The temperature drift coefficient and electromechanical coupling coefficient of the finished lithium tantalate wafer were tested respectively. The test results are shown in Table 1.
[0040] Example 2
[0041] S1, evenly placing 60 g of lithium tantalate polycrystalline material with a molar ratio of lithium to tantalum of 60:40 into the bottom of the first crucible;
[0042] S2, placing two platinum wires on the lithium tantalate polycrystalline material, and placing a Y42° lithium tantalate wafer with a thickness of 0.5 mm obtained by annealing at 600° C. for 20 hours on the platinum wires;
[0043] S3, placing the sealed first crucible in a second crucible with the bottom covered with lithium tantalate polycrystalline material;
[0044] S4. Placing the second crucible in a heat treatment furnace, heat treating at 1320° C. for 30 hours for diffusion, and obtaining a finished lithium tantalate wafer with a Li ion concentration of 49.80% inside the wafer.
[0045] The temperature drift coefficient and electromechanical coupling coefficient of the finished lithium tantalate wafer were tested respectively. The test results are shown in Table 1.
[0046] Example 3
[0047] S1, evenly placing 80 g of lithium tantalate polycrystalline material with a molar ratio of lithium to tantalum of 60:40 into the bottom of the first crucible;
[0048] S2, placing two platinum wires on the lithium tantalate polycrystalline material, and placing a Y42° lithium tantalate wafer with a thickness of 0.5 mm obtained by annealing at 700° C. for 20 hours on the platinum wires;
[0049] S3, placing the sealed first crucible in a second crucible with the bottom covered with lithium tantalate polycrystalline material;
[0050] S4. Placing the second crucible in a heat treatment furnace, heat treating at 1320° C. for 60 hours for diffusion, and obtaining a finished lithium tantalate wafer with a Li ion concentration of 49.96% inside the wafer.
[0051] The temperature drift coefficient and electromechanical coupling coefficient of the finished lithium tantalate wafer were tested respectively. The test results are shown in Table 1.
[0052] Example 4
[0053] S1, evenly placing 120 g of lithium tantalate polycrystalline material with a molar ratio of lithium to tantalum of 51:49 into the bottom of the first crucible;
[0054] S2, placing two platinum wires on the lithium tantalate polycrystalline material, and placing a Y42° lithium tantalate wafer with a thickness of 0.5 mm obtained by annealing at 700° C. for 20 hours on the platinum wires;
[0055] S3, placing the sealed first crucible in a second crucible with the bottom covered with lithium tantalate polycrystalline material;
[0056] S4. Placing the second crucible in a heat treatment furnace, heat treating at a temperature of 1200° C. for 100 hours for diffusion, and obtaining a finished lithium tantalate wafer with a Li ion concentration of 49.52% inside the wafer.
[0057] The temperature drift coefficient and electromechanical coupling coefficient of the finished lithium tantalate wafer were tested respectively. The test results are shown in Table 1.
[0058] Table 1 Test results of temperature drift coefficient and electromechanical coupling coefficient of lithium tantalate wafer
[0059] Example Temperature drift coefficient Electromechanical coupling coefficient Example 1 -21.23ppm / ℃ 8.4% Example 2 -30.23ppm / ℃ 8.0% Example 3 -34.23ppm / ℃ 7.9% Example 4 -31.23ppm / ℃ 7.92%
[0060] It can be seen from the above examples that the lithium tantalate wafer with a Li ion concentration of 49.75% inside the wafer obtained in Example 1 has the highest electromechanical coupling coefficient and the lowest temperature drift coefficient.
[0061] By comparing Example 1 with Example 2, it can be seen that when the Li ion concentration inside the wafer is higher than 49.75%, the electromechanical coupling coefficient decreases and the temperature drift coefficient increases.
[0062] By comparing Example 1 with Example 4, it can be seen that when the Li ion concentration inside the wafer is lower than 49.75%, the electromechanical coupling coefficient increases and the temperature drift coefficient decreases.
[0063] By comparing Example 2 and Example 3, it can be seen that by adjusting the quality of lithium tantalate polycrystalline material, the lithium content in lithium tantalate wafers with the same composition can be adjusted, thereby preparing lithium tantalate wafers with different lithium ion concentrations.
[0064] By comparing Example 1 with Example 4, it can be seen that by adjusting the lithium ion concentration of the lithium tantalate polycrystalline material, the lithium content in the lithium tantalate wafers with the same composition can be adjusted, thereby preparing lithium tantalate wafers with different lithium ion concentrations.
[0065] It can be seen from the embodiments provided in the present application that the embodiments of the present application adjust the lithium ion concentration and mass in the lithium tantalate polycrystalline material, and then adjust the lithium content in the lithium tantalate wafers with the same composition, so as to prepare lithium tantalate wafers with different lithium ion concentrations, among which the lithium tantalate wafers with a lithium ion concentration of 49.6% to 49.75% have a high electromechanical coupling coefficient and a low temperature drift coefficient, and their acoustic performance is better than the acoustic performance of existing lithium tantalate wafers, and can better adapt to the higher performance requirements for surface acoustic wave filters in the 5G era.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium tantalate wafer, characterized in that: The lithium ion concentration inside the lithium tantalate wafer is 49.6% to 49.75%.
2. A method for preparing a lithium tantalate wafer, characterized in that: include: 50 g to 200 g of lithium tantalate polycrystalline material is evenly placed in the bottom of the first crucible; Placing two platinum wires on the lithium tantalate polycrystalline material, and placing a lithium tantalate wafer with the same composition on the platinum wires; Placing the sealed first crucible in a second crucible with the bottom covered with lithium tantalate polycrystalline material; The second crucible is placed in a heat treatment furnace and heat treated at a temperature of 1190° C. to 1320° C. for 10 to 150 hours for diffusion to obtain a finished lithium tantalate wafer.
3. The preparation method according to claim 2, characterized in that: Before placing the lithium tantalate wafer with the same composition on the platinum wire, the method further comprises: The lithium tantalate wafer with the same composition is annealed at a temperature of 500° C. to 800° C.
4. The preparation method according to claim 2, characterized in that: Before placing the lithium tantalate wafer with the same composition on the platinum wire, the method further comprises: Growing lithium tantalate single crystals with the same composition by Czochralski method; The lithium tantalate single crystal with the same composition is pretreated to obtain the lithium tantalate wafer with the same composition.
5. The preparation method according to claim 2, characterized in that: Before placing the sealed first crucible into the second crucible with the bottom covered with lithium tantalate polycrystalline material, the method further comprises: placing a crucible cover on the first crucible to seal it; After placing the sealed first crucible in the second crucible with the bottom covered with lithium tantalate polycrystalline material, the method further comprises: The third crucible is placed upside down on the sealed first crucible to isolate the first crucible from the lithium tantalate polycrystalline material.
6. The preparation method according to claim 2, characterized in that: The molar ratio of lithium to tantalum in the lithium tantalate polycrystalline material is (50-70):(50-30).
7. The preparation method according to claim 2, characterized in that: The thickness of the lithium tantalate wafer with the same composition is 0.2 mm to 1.2 mm.
Citation Information
Patent Citations
Production method of 8-inch lithium niobate crystal
CN111206282A
Method for vapor balance growth of BaGa2GeSe6 single crystal
CN115182050A
Method of using low melting point fusant as sealing material to prevent evaporation of lead oxide
CN1442390A
Method for producing lithium tantalate single crystal
JP2007261910A
